High‐resolution optical mapping of gastric slow wave propagation. Issue 1 (20th August 2018) - Zhang, Hanyu; Yu, Han; Walcott, Gregory P.; Paskaranandavadivel, Niranchan; Cheng, Leo K.; O'Grady, Gregory; Rogers, Jack M.
Abstract: Background: Improved understanding of the details of gastric slow wave propagation could potentially inform new diagnosis and treatment options for stomach motility disorders. Optical mapping has been used extensively in cardiac electrophysiology. Although optical mapping has a number of advantages relative to electrical mapping, optical signals are highly sensitive to motion artifact. We recently introduced a novel cardiac optical mapping method that corrects motion artifact and enables optical mapping to be performed in beating hearts. Here, we reengineer the method as an experimental tool to map gastric slow waves. Methods: The method was developed and tested in 12 domestic farm pigs. Stomachs were exposed by laparotomy and stained with the voltage‐sensitive fluorescence dye di‐4‐ANEPPS through a catheter placed in the gastroepiploic artery. Fiducial markers for motion tracking were attached to the serosa. The dye was excited by 450 or 505 nm light on alternate frames of an imaging camera running at 300 Hz. Emitted fluorescence was imaged between 607 and 695 nm. The optical slow wave signal was reconstructed using a combination of motion tracking and excitation ratiometry to suppress motion artifact. Optical slow wave signals were compared with simultaneously recorded bipolar electrograms and suction electrode signals, which approximate membrane potential. Key Results: The morphology of optical slow waves was consistent with previously published microelectrode recordings and simultaneously recorded suction electrode signals. The timing of the optical slow wave signals was consistent with the bipolar electrograms. Conclusions and Inferences: Optical mapping of slow wave propagation in the stomach is feasible. Abstract : We describe an optical mapping method to track slow wave propagation on the serosal surface of large animal stomachs in vivo.